Hsa‐miR‐27a‐3p and epidermal growth factor receptor expression analysis in glioblastoma FFPE samples. Issue 5 (7th October 2020) - Salmani, Tayyebali; Ghaderian, Sayyed Mohammad Hossein; Hajiesmaeili, Mohammadreza; Rezaeimirghaed, Omidvar; Hoseini, Mahshid Sadat; Rakhshan, Azadeh; Nasiri, Mohammad Javad; Ghaedi, Hamid; Akbarzadeh, Reza
Abstract: Aim: Glioblastoma multiforme (GBM) is the most invasive type of glial tumors. MicroRNAs as the small, noncoding RNAs have been revealed that play an important role in tumorigenic processes. So, they may be used as potential biomarkers for detection and prognosis of cancers at the early stages. In addition, they can be applied as therapeutic targets. In the present study, the expression levels of hsa‐miR‐27a‐3p and EGFR were investigated in GBM. Methods: Real‐time RT‐PCR was applied to evaluate hsa‐miR‐27a‐3p and EGFR expressions in the formalin‐fixed paraffin‐embedded (FFPE) tissue samples obtained from 50 GBM and 50 normal people. Results: The expression level of hsa‐miR‐27a‐3p and EGFR was significantly different between cases and controls. Positive association was found between gene expressions and immunohistochemistry markers, such as Ki67 and glial fibrillary acidic protein, except for IDH1 status. Conclusion: We showed the association of hsa‐miR‐27a‐3p and EGFR with GBM and it can be concluded that they have a promising potential to use as primary cancer biomarkers.